Geometric reconstruction of the left ventricle on a beating heart through a minimally invasive approach from the left anterolateral thoracotomy: case report - Aigumov, R. N.; Donakanyan, S. A.; Merzlyakov, V. Yu; Skopin, A. I.; Baichurin, R. K.; Panagov, Z. G.; Sizhazhev, E. M.; Shvartz, V. A.; Golukhova, E. Z. (Frontiers in Cardiovascular Medicine, 2024)
Despite the widespread use of mini-invasive treatment methods in cardiac surgery, their use in post-infarction myocardial aneurysms of the left ventricle is not of frequent occurrence. In this clinical case, we used left anterolateral thoracotomy and “eating heart” technique to correct the post-infarction left ventricle aneurysm with ventricular thrombosis using the Dor method in a 66-year-old patient. This technique created opportunity to perform safely and effective the planned reconstruction of the left ventricle with less trauma, as well as to ease the postoperative course and recovery of the patient, reduce hospitalization time.